Performance Evaluation of Location-based Conditional Handover Scheme using LEO Satellites - Lee, Jongtae; Lee, Wonjae; Kim, Jae Hyun (International Conference on ICT Convergence, 2023)
The high velocity of LEO satellites can result in frequent handover (HO) in non-terrestrial networks (NTN). In a satellite environment, due to the high altitude, the signal strength variation between the cell center and the cell edge is very small. As a result, when using the signal strength-based HO, there are challenges in selecting an appropriate cell during HO. To address this issue, we proposed a location-based conditional HO (CHO) approach instead of the signal strength-based method. This approach uses the distance between the reference location of the cell and the user equipment (UE) to make HO decisions. This allows the UE to choose a suitable cell. Additionally, through an analysis based on the variation of signal strength with the UE's position within the cell and the distance change between the UE and the cell center, the distance offset is determined. Simulation results demonstrate that the proposed approach, when compared to the conventional method, can reduce radio link failure (RLF) and HO failure (HOF).
Keywords: Cell centers; Hand over; LEO satellite; Location based; Mobility; Non-terrestrial network; Performances evaluation; Signal strengths; Terrestrial networks; User equipments; handover; LEO satellites; mobility; non-terrestrial networks